if m=4 n=-3, solve: m^-n+3m^2*n-52

Question

if m=4 n=-3, solve:
m^-n+3m^2*n-52

in progress 0
Edana Edana 5 months 2021-08-19T09:22:56+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-19T09:24:12+00:00

    Answer:

    (4^−3)+3(4^2)(−3)−52

     -64 + 48 (-3 -52)

    -64 + (48 x -55)

    -64 – 2640

    -2704

    I’m not sure if that’s the right equation, I hope I captured it correctly from your question.

    Step-by-step explanation:

    0
    2021-08-19T09:24:34+00:00

    Sorry if i’m wrong

    The Answer ⤵️

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )